1994
DOI: 10.1007/bf00033887
|View full text |Cite
|
Sign up to set email alerts
|

Catharanthine and ajmalicine synthesis in Catharanthus roseus hairy root cultures

Abstract: Two year old, transformed root cultures of Catharanthus roseus accumulate ajmalicine and catharanthine (0.57 and 0.36 mg g-I DW, or 7.0 and 3.0 mg I-I, respectively). Changes in the concentration of the medium components, as well as the addition of hydrolytic enzymes and biotic elicitors, were used as strategies to increase these alkaloid yields. Regarding the components of the medium, the results obtained, when sucrose was raised from 3 to 4.5%, are noteworthy. The nitrogen source induced differential respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(23 citation statements)
references
References 27 publications
(17 reference statements)
1
21
1
Order By: Relevance
“…1a). Ajmalicine and catharanthine were also the main alkaloids in the J1 hairy roots line (Vázquez-Flota et al 1994). Both showed a Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1a). Ajmalicine and catharanthine were also the main alkaloids in the J1 hairy roots line (Vázquez-Flota et al 1994). Both showed a Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The relationship of the trend of FW/DW to substrate depletions was also very striking. Though 2%-6% sucrose is commonly examined for influence of sucrose on output of C. roseus hairy roots (Jung et al, 1992;Parr et al, 1988;Shanks and Bhadra, 1997;Toivonen et al, 1991;Vasquez-Flota et al, 1994), effects of this and other nutrients on biomass are not often quantified by substrate yield coefficients and specific rates from transient data. Jung et al (1992) have reported biomass yield coefficients on glucose, fructose, and sucrose determined by an unspecified method: 0.53 g/g with 3% sucrose and 1/3 Shenk-Hildebrandt nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…Published reports of hairy root cultures of C. roseus have focused largely on ajmalicine, serpentine, and/or catharanthine in a variety of short-and medium-term studies (Ciau-Uitz et al, 1994;Islas et al, 1994;Parr et al, 1988;Toivonen et al, 1989Toivonen et al, , 1990Vasquez-Flota et al, 1994). Though tabersonine is known to occur in hairy roots (Parr et al, 1988;Toivonen et al, 1989), its kinetics of accumulation has not been studied.…”
Section: Introductionmentioning
confidence: 95%
“…It is also observed in case of Catharunthus roseus hairy root cultures where no net change in the alkaloid content was observed with the changes in the concentration of vitamins. 26 Nevertheless, enhancement in secondary metabolite productivity had also been reported earlier through supplementation of the half strength B5 medium formulation with the vitamin composition of the full strength media. 27 In case of Polygonum tinctorium 22 hairy root cultures, lower pH levels influenced the biomass productivities in a similar fashion.…”
mentioning
confidence: 81%